Assessment of Nursing Care through Intravenous Solution Therapy among Children - Rifaie Yaseen Hameed; Abdulkhaliq Shakir Yousif (College of Nursing,University of Mosul, 2018)
Intravenous (IV) solution is a scarce human resource and ensuring its safety and clinical effectiveness requires investment - both human and financial. IV solution therapy is an essential part of patient care. When used correctly, it saves life and improves health. The nurse has an important and effective role in implementation and monitoring of care while IV solution infusion. Methods and Materials: This descriptive study was carried out in internal medicine wards and emergency departments in Ibn-AL-Atheer teaching hospital, Ibn-Sina teaching hospital and AL-Khansa'a teaching hospital in Mousl city for the period from 15th October / 2012 to 10th September / 2013 to assess the nursing care throughout procedure of IV solution infusion therapy for children. The sample of the study were convenience composed of (104) nurses while performing intravenous solution infusion in the above hospitals' wards. A special observational tool was prepared utilizing available related literatures . Content Validity of the tool was done through opinions of a panel of (24) experts, while the reliability of tool was done through a pilot study that were r(Pre) = 0.77 , r(Intra) = 0.71 , r(Post) = 0.78 , and r(Total) = 0.74. Results: The acceptable levels of the three stages of procedure as a results of the study were as; Pre-procedure=98.4%, Intra-procedure=70.6% and Post-procedure=52.6%. Conclusion: The study concluded negligence in some activities are dangerous and can be fatal, heedlessness in case the solution is suitable to be infused or not, and heedlessness or ignorance of sterilization and disinfection. The study recommended that the nurses working in Intravenous solution infusion must be highly qualified and efficient in regard to IV therapy. Standardized guidelines in respect to sterilization and disinfection throughout each procedure.